Keputusan Pembiayaan dan Keputusan Investasi Terhadap Nilai Perusahaan Dimoderasi Kinerja Keuangan - Sunita Dasman; Dian Sulistyorini Wulandari; Widiastuti Widiastuti (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
Purpose- This research examines financing and investment decisions on company value related to financial performance.Method – This research uses moderated regression analysis (MRA) on the consumer goods industry period 2013 – 2022. Samples were taken using a purposive sampling method, and found 16 companies. Debt financing, dividend distribution and investment are moderated by financial performance on company value.Findings - Increased debt contingent on financial performance reduces firm value. Investment decisions are influenced by economic performance to increase company value. The role of financial performance needs to be visible in dividend policy on company value.Originality (Novelty) – Combining financing and investment decisions and moderating them with financial performance can provide a deeper understanding of how companies can optimize enterprise value through integrated strategic financial choices..Implication - Companies should consider their financial performance so that financing and investment can be positive signals for investors to increase company value. Debt financing should reduce company value when the company obtains more profit.